A prospective randomised controlled trial investigating the impact of a musculoskeletal injury prevention warm-up program for youth badminton: A preliminary study - Phomsoupha, M.; Tran, A.; Guermont, H. (Journal of Sports Sciences, 2025)
There are warm-up programs designed to reduce injuries for various sports; however, no study has been conducted on the development of a protocol for preventing injuries in badminton. The purpose of this study was to investigate the effectiveness of a prevention warm-up program (PreventiBad) in reducing injury rates among youth badminton players. A cluster randomised controlled trial was conducted, involving 273 youth badminton players (13.81 ± 2.76 years). The intervention group incorporated the program as part of their warm-up during training sessions, while the control group adhered to their usual warm-up. The participants were monitored over an 8 weeks period, with primary outcome measures including the incidence of overall injuries, typology and severity. The rate of adherence to the intervention program was assessed as a secondary outcome. A total of 14 injuries were reported among 147 players in the control group in 3440.50 h of exposure (4.07 injuries/1000 h), and a total of 6 injuries were reported across 126 players within the intervention group in 4865.00 exposure hours (1.23 injuries/1000 h). The Injury Risk Ratio was 0.30 (95%CI 0.12 to 0.75). Results indicated that the use of PreventiBad in the intervention group led to a 70% reduction compared to the control group.